2021
DOI: 10.3389/fphar.2021.774884
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evidence for Intrahepatic Cholestasis of Pregnancy Treatment With Traditional Chinese Medicine Therapy: A Network Meta-Analysis

Abstract: Background: Intrahepatic cholestasis of pregnancy (ICP) seriously threatens the health of pregnant women and newborns. A various number of Chinese prescriptions and patent medicines combined with ursodeoxycholic acid (UDCA) are used for treating ICP in China. However, there are still many doubts in choosing the suitable therapeutic drugs for the treatment of ICP in clinical practice.Methods: Several electronic databases, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…2,3 Additionally, TCM is also used in the treatment of gestational diseases, such as influenza/cold, 4 gestational diabetes mellitus, 5 hypertension 6 and intrahepatic cholestasis. 7 These findings, together with the claim that TCM is natural and safe, 8 have been greatly promoted by pregnant women in mainland China (10.1%), 4 Taiwan (20.2%-35%) 9 and Hong Kong (55.8%). 10 Thalidomide and diethylstilboestrol result in severe birth defects, therefore health professionals have been concerned about the safety of other medicines during pregnancy.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…2,3 Additionally, TCM is also used in the treatment of gestational diseases, such as influenza/cold, 4 gestational diabetes mellitus, 5 hypertension 6 and intrahepatic cholestasis. 7 These findings, together with the claim that TCM is natural and safe, 8 have been greatly promoted by pregnant women in mainland China (10.1%), 4 Taiwan (20.2%-35%) 9 and Hong Kong (55.8%). 10 Thalidomide and diethylstilboestrol result in severe birth defects, therefore health professionals have been concerned about the safety of other medicines during pregnancy.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have identified that TCM showed efficiency or additional utility in the preparation and maintenance of pregnancy 2,3 . Additionally, TCM is also used in the treatment of gestational diseases, such as influenza/cold, 4 gestational diabetes mellitus, 5 hypertension 6 and intrahepatic cholestasis 7 . These findings, together with the claim that TCM is natural and safe, 8 have been greatly promoted by pregnant women in mainland China (10.1%), 4 Taiwan (20.2%–35%) 9 and Hong Kong (55.8%) 10 …”
Section: Introductionmentioning
confidence: 99%
“…Advantage from this is a more individualized treatment plan. In China, TCM are widely applied with combination of UDCA for the treatment of ICP ( Jiang et al, 2021 ; Wei et al, 2022 ). The treatment for ICP mainly focused hepatoprotection and promoting circulation of bile.…”
Section: Hepatoprotective Agents In the Management Of Icpmentioning
confidence: 99%
“…A network meta-analysis by included 38 RCTs exploring the effect of Yinchenhao in ICP pregnancies. Their results demonstrated that when compared with UDCA used alone, Yinchenhao decoction plus UDCA dramatically reduced the serum levels of bile acid, ALT, and AST ( Jiang et al, 2021 ). Recent clinical trials of Yinchenhao in ICP pregnancies are summarized in Supplementary Tables S1, S2 ( Wang et al, 2019 ; Chen et al, 2020 ; Xu et al, 2021 ; Zhu, 2021 ) ( Supplementary Tables S1, S2 ).…”
Section: Hepatoprotective Agents In the Management Of Icpmentioning
confidence: 99%
“…기존의 고찰 문헌들에도 이러한 연구들이 포함 되어 있었다29,30,[34][35][36] . 따라서, 기존 연구들에서 제시 된 결과들을 다시 확인하여 정리하고, 아울러 인진 호탕이 투여될 수 있는 간담도계 질환들 전반에 대하여 보편적으로 기대할 수 있는 효과크기를 산 정해보고자 하였다.…”
unclassified